THE IMPORTANCE OF THE WORK “TARIHI RASHIDIY” IN STUDYING THE ACTIVITIES OF ZAHIRIDDIN MUHAMMAD BABUR - Sharipova Dilnavoz (Western European Studies, 2025)
This article describes the relationship between Babur’s cousin and contemporary, historian and commander Mirzo Muhammad Haidar, who lived in the 16th century, and Zahiriddin Muhammad Babur, as well as some events in Babur’s life, his character and other aspects in the work “Tarihi Rashidiy”, as well as information not found in other works, and the importance of these facts in studying the history of Babur
Keywords: Mirza Muhammad Haidar; Zahiriddin Muhammad Babur; political situations in the 15th-16th centuries